MODE OF DELIVERY, HOSPITAL OWNERSHIP AND PREDICTORS MATERNITY LENGTH OF STAY IN TWO HOSPITALS IN JAKARTA - Opitasari, Cicih (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Length of stay (LOS) is one of the most common indicator used for hospital performance assessment. The longer LOS for mothers giving birth can increase the risk of nosocomial infections and cause some psychological problems. Aims: This study aims to analyze the determinants of maternal length of stay which can be used to evaluate the hospital efficiency and quality care improvement. Methods: The cross-sectional study was conducted in two hospitals in Jakarta. We used the medical records of women who underwent delivery during the period of January 1 to December 31, 2011. Multivariate linear regression analysis with stepwise method was used to predict length of stay. Results: The study found 2727 patients met the inclusion criteria and were included in the analysis. The overall mean length of hospital stay was 3 days and the mean of motherâs age was 29,9 years old. Among all of the covariates, mode of delivery had largest impact on LOS, with cesarean section increasing LOS by 1.2 days on average (Coef=1,21; P=0,000), followed by hospital ownership with private hospital reducing LOS 0,79 days on average (Coef = 0,79; P=0,000). Conclusion: Mode of delivery and hospital ownership were the strong predictors for maternal length of stay in two hospitals in Jakarta.Â